If or When? Uncertainty's Role in Anxious Anticipation - (:unkn) unknown (My University, 2016)
Uncertainty is often associated with subjective distress and a potentiated anxiety response. Occurrence uncertainty (OU), or the inability to predict if a threat will occur, has never been compared experimentally with temporal uncertainty (TU), or the inability to predict when a threat will occur. The current study aimed to 1) directly compare the eye-blink startle responsivity of OU and TU, 2) develop a more effective task for isolating uncertain anticipation, and 3) better understand the relationship between individual differences in the intolerance of uncertainty and uncertain anticipation startle responsivity. The novel study showed that OU anticipation is more anxiety provoking than certain threat, but TU anticipation is superior at eliciting anxiety overall. This suggests that in the context of uncertainty, there must be some level of certainty or threat proximity to elicit a robust anxiety response. Individual difference in the intolerance of uncertainty were not related to anticipatory startle responsivity.
Keywords: Anticipation; Anxiety; NPU; Startle; Threat; Uncertainty